A robust and semi-automatic quantitative measurement of patellofemoral instability based on four dimensional computed tomography. (April 2020) - Chen, Hao; Kluijtmans, Leo; Bakker, Max; Dunning, Hans; Kang, Yan; van de Groes, Sebastiaan; Sprengers, André M.J.; Verdonschot, Nico
Highlights: An automatic method to determine the anatomical coordinate frame of femur and tibia. An automatic method to determine the landmarks of TT-TG (tibial tubercle – trochlear groove) and PC-TG (patellar centre – trochlear groove) distance. A dynamic quantitative description of TT-TG and PC-TG distance in a patient group (15 legs). The added value of quantitative measurement based on 4DCT compared to traditional CT scan. Abstract: Patellofemoral instability is a motion related disease, featured as the patella dislocating from the trochlear groove. Four dimensional computed tomography (4DCT) enables full assessment of the patellofemoral movement. Nevertheless, the quantitative measurements of patellofemoral instability are still under research and currently of limited practical use. The aim of this study is to develop a robust and semi-automatic workflow to quantitatively describe the patellofemoral movement in a patient group of eight suffering from patellofemoral instability. The initial results show agreement with manual observations of the tibial tubercle – trochlear groove (TT-TG) distance in routine practice, and the possibility to evaluate both TT-TG distance and patellar centre – trochlear groove (PC-TG) distance dynamically during active flexion-extension-flexion movement of the knee.